Changed Tendencies in Research Issues on Motivation for Foreign Languages Learning (Review for 2021) - Tsalikova I.K; Pakhotina S.V; Kungurova I.M; Slizkova E.V; Voronina E.V (Moscow State University of Psychology and Education, 2022)
The COVID-19 pandemic has changed social and educational environment, which affected the educational process participants and the research directions. The article shows the changes in the direction of studies dealing with the issues of university students` foreign languages learning motivation, published in 2021. Researching is still aimed at studying the online environment and its potential. Its high potential to develop the motivation is stated, but the lack of participants` experience of its using prevents its full acceptance so far. The problems of maintaining personal interaction between a teacher and students; overcoming stress and anxiety; adaptation to the virtual learning environment and their impact on the motivation are of research interest. Another part of the research works is traditionally devoted to the components of educational motivation, strategies for their managing, etc. The results of the analysis will help to understand how well the problem has been studied and determine the direction of future research. Портал психологических изданий PsyJournals.ru - https://psyjournals.ru/en/journals/psyedu/archive/2022_n3/Tsalikova_et_al [Changed Tendencies in Research Issues on Motivation for Foreign Languages Learning (Review for 2021) - Psychological-Educational Studies - 2022. Vol. 14, no. 3]